The impact of insole wedge height on knee alignment, joint space width, and patient-reported outcomes in medial knee OA - Bashar Al Qaroot; Mohammad Sobuh; Mohammad Hamdan; Jihad Al Ajlouni; Farah Al-Imyan; Eman Al-Laham; Ibrahim Altubasi; Aws Khanfar (PLOS One, 2026)
Introduction Lateral wedge insoles (LWIs) are a recommended conservative treatment for medial knee osteoarthritis (OA), yet the optimal wedge height remains unclear. This randomized controlled trial evaluated the effects of different LWI heights on radiographic outcomes in patients with medial knee OA. Methods This study employed a randomized, controlled, parallel-arm design with a sequential, within-subject dose-escalation intervention arm. Thirty-four participants with mild-to-moderate medial knee OA (Kellgren- Lawrence grade